Determinants of weight gain in pregnant women attending a public prenatal care facility in Rio de Janeiro, Brazil: a prospective study, 2005-2007. - Rodrigues, P; Lacerda, E; Schlüssel, M; Spyrides, M; Kac, G (2008)
The objective of this study was to evaluate the determinants of weight gain during pregnancy. The study adopted a prospective cohort design with four follow-up waves and included a sample of 255 pregnant women that received prenatal care at a public health care facility in Rio de Janeiro, Brazil. A mixed-effects linear longitudinal regression model was used, having as the dependent variable the weight assessed in four follow-up waves, and as independent variables: demographic, socioeconomic, reproductive, behavioral, and nutritional data. Mean weight gain was 0.413kg per gestational week, consistent with recommendations by the Institute of Medicine. Per capita family income and smoking were associated with total weight gain during gestation. According to the longitudinal multiple linear regression model, age (beta = 0.6315), menarche (beta = -2.3861), triglycerides (beta = 0.0437), blood glucose (beta = 0.1544), and adequacy of energy consumption (beta = -0.0642) were associated with gestational weight gain. Special attention should be given to these sub-groups, due to increased risk of excessive weight gain.